2020
DOI: 10.1177/0954405420927561
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cutting parameters on micro-topography of frequency features extracted from the machined KH2PO4 surfaces

Abstract: Using reasonable cutting parameters of machining process is an effective and convenient means of improving the topography of the machined surfaces. In this study, the methods to find optimised cutting parameters can be obtained by studying the relationship between the cutting parameters and the micro-topography of frequency features in the machined KH2PO4 surfaces. Using the power spectral density and continuous wavelet transform methods, the 2D micro-topographies of frequencies corresponding to different cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…According to Gurau and Ayrilmis (2019), the surface roughness of WPCs is affected by the composition of the raw materials used for manufacturing. Pang et al (2020) believed that cutting parameters are the main factors determining the surface morphology of the workpiece. When processing oak wood, Ugulino and Hernandez (2017) found that the feed speed was the most influential cutting parameter affecting the surface roughness, and the surface roughness increased with an increase in the feed speed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gurau and Ayrilmis (2019), the surface roughness of WPCs is affected by the composition of the raw materials used for manufacturing. Pang et al (2020) believed that cutting parameters are the main factors determining the surface morphology of the workpiece. When processing oak wood, Ugulino and Hernandez (2017) found that the feed speed was the most influential cutting parameter affecting the surface roughness, and the surface roughness increased with an increase in the feed speed.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the topological matrix of grinding wheel surface topography and the depth of cut is the basis for judgment. The active cutting edge can be determined by using equation (15), as follows:…”
Section: Mathematical Model Of Abrasive Trajectorymentioning
confidence: 99%
“…13,14 In grinding, the final surface roughness of the workpiece is formed by the interference of the movement of multiple abrasives and is affected by the grinding parameters. 15 The reciprocation of the ironing of abrasives in TUAG reduces the height of the residual material on the processed surface. Recent studies have found that the surface roughness decreases under ultrasonic grinding conditions, but the effects of ultrasonic vibration are not apparent with uprated process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To bridge this gap, a great number of efforts have been made to evaluate machined surface morphologies during the past decades. For instance, the power spectrum density (PSD) [28,29] has been used to extract the frequency information from machined surfaces, while the continuous wavelet method [30] has been employed to analyze the dynamic evolution process of the dominated frequency with the change of machining distance. These methods are all based on the Fast Fourier Transform analysis of the surface contour data, which are similarly affected by the measurement conditions.…”
Section: Introductionmentioning
confidence: 99%